2014
DOI: 10.5935/medicalexpress.2014.04.02
|View full text |Cite
|
Sign up to set email alerts
|

Pain assessment in patients with adolescent idiopathic scoliosis at different stages of disease evolution

Abstract: OBJECTIVE:The correlation between pain complaints and the severity of the spinal curvature in adolescent idiopathic scoliosis remains controversial. The aim of this study was to evaluate the presence and intensity of back pain in adolescent idiopathic scoliosis patients at different stages of the disease. METHODS: Sixty-four individuals participated in this study with scoliotic curves (Cobb angles) between 20 and 90 degrees. Patients were divided into four groups according to the scoliotic curves: Group 1 (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
4
0
5
Order By: Relevance
“…A preliminary study reported a higher complaint rate of back pain in patients with scoliosis than in healthy individuals. 38 In the natural course of scoliosis, due to asymmetrical loading on the spine, intervertebral disc and facet joint degeneration and differences in spinal muscle length occur, leading to chronic pain. Therefore, for the conservative treatment of AIS, pain relief is considered to be important.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study reported a higher complaint rate of back pain in patients with scoliosis than in healthy individuals. 38 In the natural course of scoliosis, due to asymmetrical loading on the spine, intervertebral disc and facet joint degeneration and differences in spinal muscle length occur, leading to chronic pain. Therefore, for the conservative treatment of AIS, pain relief is considered to be important.…”
Section: Discussionmentioning
confidence: 99%
“…6 Algunos autores lo han atribuido a la carga asimétrica que provoca una degeneración prematura de facetas y discos intervertebrales y acortamiento de musculatura. 6,37,38 Sin embargo, no se conoce con exactitud el mecanismo por el que se habría mejorado esta variable, que puede venir determinado por la mejora de la flexibilidad de la columna y de los tejidos adyacentes 39 o por la propia liberación de sustancias moduladoras del dolor por el propio ejercicio. 40 Un artículo observó mejoras en la capacidad pulmonar.…”
Section: Discussionunclassified
“…5 Pese a no ser un factor clínico principal, l o s p a c i e n t e s c o n E I A p u e d e n presentar dolor; son más proclives a desarrollarlo en mayores grados de ángulo de Cobb. 6 Estudios de prevalencia han mostrado que el dolor se presenta entre el 27% y el 59% de los casos. 5,7 Además, se pueden asociar otros problemas, como la restricción d e l a v e n t i l a c i ó n , l a d e b i l i d a d de la musculatura respiratoria, la disminución de la calidad de vida 8 e, incluso, problemas psicológicos.…”
Section: Introductionunclassified
“…6 Some authors have attributed them to the asymmetric burden that causes early intervertebral disc and facet degeneration and shortening of the muscles. 6,37,38 However, the mechanism that leads to the improvement in such outcome measure is not known accurately, given that it may be the result of an improved flexibility in the spine and adjacent tissues 39 or the release of pain modulatory substances resulting from exercise itself. 40 An article described improvements in pulmonary capacity.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although it is not the main clinical factor, patients with AIS may have pain; they are more prone to pain when the degree of Cobb's angle is higher. 6 Studies on AIS prevalence have demonstrated that between 27% and 59% of patients suffer pain. 5,7 In addition, it may be associated with other conditions, such as restricted ventilation, respiratory muscle weakness, reduced quality of life, 8 and even psychological problems.…”
Section: Introductionmentioning
confidence: 99%